PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE TRADING PLACES BESERTA HANDOUT TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 3 KOTA SOLOK - Okri Maiza, Yuki; Rismen, Sefna; Yunita, Alfi (Pendidikan Matematika, 2014)
ABSTARCTÂ This research was conducted based on the phenomena indicating that the students had less skill in solving the mathematics problem and were unable to develo their own ideas. This research was aimed at revealing whether the mathematics consetual understanding of the students taught by using Trading Places active strategy was better than that of sudents taught by using convetional learning. This was an exerimental research which used random toward the subject design. The populatioan of the research was the students in clas VIII of SMPN 3 Kota Solok registered in academic year 2013/2014. The instruments of the reseach were a posttest and observation sheet for the studentsâ activities. Th data collected was analyzed by using t-test. Based on the results of the final test data analysis can be found thitung= 2,24 and ttabel=1,679, so that hypothesis is approved. Based on the result of data analysis it was know that the mathematics consetual understanding of the students taugt by using Trading Places active strategy was better than that of students taught by using conventional learning in class VII of SMPN 3 Kota Solok registered in academic year 2013/2014.